2007
DOI: 10.1002/chem.200700154
|View full text |Cite
|
Sign up to set email alerts
|

Double Aromaticity in Monocyclic Carbon, Boron, and Borocarbon Rings Based on Magnetic Criteria

Abstract: The double-aromatic character of selected monocyclic carbon, boron, and borocarbon rings is demonstrated by refined nucleus-independent chemical shift (NICS) analyses involving the contributions of individual canonical MOs and their out-of-plane NICS tensor component (CMO-NICS(zz)). The double aromaticity considered results from two mutually orthogonal Hückel p AO frameworks in a single molecule. The familiar pi orbitals are augmented by the in-plane delocalization of electrons occupying sets of radial (rad) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 151 publications
5
52
0
1
Order By: Relevance
“…Bonding character in the σ-system of the cation is increased with increased bond angle at the phenyl carbon consistent with Walsh's rules. A similar increase in bond angle is found in the double aromatic [39] C 6 H 3 + cation. The VIF treatment of the σ-system for this cation is shown in Figure 26.…”
Section: Depiction Of Ring Systemssupporting
confidence: 77%
“…Bonding character in the σ-system of the cation is increased with increased bond angle at the phenyl carbon consistent with Walsh's rules. A similar increase in bond angle is found in the double aromatic [39] C 6 H 3 + cation. The VIF treatment of the σ-system for this cation is shown in Figure 26.…”
Section: Depiction Of Ring Systemssupporting
confidence: 77%
“…In effect, this is mirrored on the shapes of the NICS zz -scan curves reported herein, which once again correctly predict the orbital-type of aromaticity in the isomeric benzyne molecules. [16]. It was claimed that the c-C 6 cluster is also σ-antiaromatic due to cyclic delocalization of its four lone-pair electrons.…”
Section: The Nics Zz -Scan Curves Versus the Orbital-type Of Aromaticmentioning
confidence: 99%
“…Hofmann and Berndt [90] showed that the the NICS(1) values of the double aromatic isoelectronic [c-C 6 H 3 ] + and c-C 5 BH 3 molecules are significantly larger than that of the benzene molecule due to the contribution of an additional aromatic system, namely the σ-aromatic component. Akin to c-C 6 (D 3h ) the c-C 10 (D 5h ) cluster was also proved to be a double (σ + π)-aromatic molecule with enhanced aromaticity due to an additional diatropic subsystem (the diatropic in-plane radial system) [16]. This is consistent with the estimated excitation energies of the σ-and π-type transitions (Table 10), which indicate that the σ-aromatic component should be larger than the π-aromatic one and is mirrored on the shape of the NICS zz -scan curve shown in Figure 9b.…”
Section: The Nics Zz -Scan Curves Versus the Orbital-type Of Aromaticmentioning
confidence: 99%
See 2 more Smart Citations